Identifying research priorities to improve the health of incarcerated populations: results of citizens' juries in Australian prisons - Paul L Simpson, PhD; Jill Guthrie, PhD; Jocelyn Jones, PhD; Tony Butler, ProfPhD (Elsevier, 2021)
Summary: Health disparities in incarcerated populations should guide investment in the health care and research of these communities. Although users of health-care services are important in providing input into decisions about research, the voices of people in prison are absent regarding research into their health. In this Health Policy paper, we present priorities for research into the health of people in prison according to people in prison themselves. By use of a deliberative research approach, citizens' juries were conducted in six prisons (three men's and three women's prisons) in Australia. Participants were selected following submissions of expression of interest forms that were distributed within the prisons. Prerecorded information by experts in the health of incarcerated people was shown to participants. Participants deliberated for up to 4 h before agreeing on five research priorities. All citizens' juries endorsed mental health as a number one research priority. Prison health-care services, alcohol and other drug use, education, and infectious diseases were identified as research priorities by most citizens' juries. Focal points within priorities included serious mental illness; grief and trauma; medication management; health-care service access, quality, and resources; drug withdrawal and peer support; prison-based needle and syringe programmes; and health and life skills education. If endeavours in research priority setting are to consider health equity goals, the views of our most health affected citizens need to be included.